Mobilidade urbana em Santa Maria, RS: os desafios da integração territorial em áreas de alta privação social - Rorato, Luciano Coelho (2023)
This research proposes to analyze the conditions of urban mobility in areas of high social deprivation in Santa Maria. The spatial cutout of the study is composed of 15 neighborhoods located in the north, west and east zones of the city, all crossed by the railway. The procedures used were based on bibliographic, documental and normative research, using the narrative type. In addition, the research proposed the creation of an index called Urban Mobility Index (UMI), that measures the commuting capacity of the residents in the neighborhoods studied, which is done by observing of the social conditions manifested by the Social Deprivation Index (SPI), by the conditions of the circulation roads and the access to the existing public transportation. Another procedure for primary data collection was through fieldwork to obtain knowledge of the territorial disintegration of these communities. The result found is that the low urban mobility of the residents of the neighborhoods researched is due to poor infrastructure, besides socioeconomic deprivation resulting from problems such as income, education, lack of basic sanitation that make clear the existing socio-spatial inequality. Thus, this research prepares an analysis of the expressions of land use, social conditions, access to public transportation, the conditions of the circulation roads, and finally the conditions of the urban mobility. The preliminary conclusion is that territories of high social deprivation are also characterized by a chronic situation of spatial and urban immobility, thus requiring public policies to promote territorial integration.